Evaluation of changes in blood pressure in patients submitted to dental surgical procedures - Andrade, Poliana Keller de; Balestrassi, Rayra Batista; Prando, Ricardo Henrique Nunes; Matos, Jefferson David Melo de; Nakano, Leonardo Jiro Nomura; Prado, Pedro Henrique Condé Oliveira; Lopes, Guilherme da Rocha Scalzer; Bottino, Marco Antonio; Vasconcelos, John Eversong Lucena de; Andrade, Valdir Cabral; Perez, Erick Gomes (ARCHIVES OF HEALTH INVESTIGATION, 2021)
The present study aimed to evaluate the occurrence of significant changes in systemic blood pressure (SBP) during surgical-dental procedures. A prospective study was performed with a sample of 135 randomly selected individuals who underwent surgical procedures at the Bucomaxillofacial Surgery Clinic of the Dentistry School of the ESFA (ES) between the second half of 2017 and April 2018. After consent, sociodemographic, lifestyle data, weight and height were obtained through a questionnaire, weighing and measurement, respectively. BP measurements were performed at three moments: preoperative (BP1), intraoperative (BP2) and postoperative (BP3) using a mercury column sphygmomanometer and stethoscope. Values ​​<120/80 mmHg were used as normal values. When BP1 and BP2 were compared, 63.0% remained within normal values ​​and 22.2% reached the stage of hypertension. In the comparison of BP1 and BP3, 66.7% remained normal, and only 7.4% reached the stage of hypertension. When BP2 and BP3 were compared, 53.6% remained within the normality stage and 12.2% reached the stage of hypertension. It was concluded that there were variations in blood pressure, being the largest variation found in BP2, and can be attributed to the stress caused by the surgical act, since no statistically significant connections were found between the changes in blood pressure and the anesthetics used in the research.